2012
DOI: 10.1007/s12038-012-9283-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DU145 prostate cancer cell growth by Scm-like with four mbt domains 2

Abstract: Mammalian SFMBTs have been considered to be polycomb group repressors. However, molecular mechanisms underlying mammalian SFMBTs-mediated gene regulation and their biological function have not been characterized. In the present study, we identified YY1 and methylated histones as interacting proteins of human SFMBT2. We also found that human SFMBT2 binds preferentially to methylated histone H3 and H4 that are associated with transcriptional repression. Using DU145 prostate cancer cells as a model, we showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Since SFMBT2 is found to interact with YY1, which is a mammalian ortholog of Drosophila PHO [24, 34, 35], we further confirmed interaction of SFMBT2 with YY1 in LNCaP cells (Figure 3A). Consistent with a previous report [27], we also found that SFMBT2 interacts with RING1B/RNF2 E3 ubiquitin ligase, which mediates mono-ubiquitination of H2AK119, in LNCaP cells.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Since SFMBT2 is found to interact with YY1, which is a mammalian ortholog of Drosophila PHO [24, 34, 35], we further confirmed interaction of SFMBT2 with YY1 in LNCaP cells (Figure 3A). Consistent with a previous report [27], we also found that SFMBT2 interacts with RING1B/RNF2 E3 ubiquitin ligase, which mediates mono-ubiquitination of H2AK119, in LNCaP cells.…”
Section: Resultssupporting
confidence: 55%
“…The mammalian PcG protein SFMBT2 has been shown to play an important role in prostate cancer cell growth through HOXB13 gene regulation via interaction with YY1 [24]. In this study, we further characterized the function of SFMBT2 in prostate cancer metastasis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations